Developing domino card learning media for the fourth grade of elementary school students - Salsa Gitamayu; Husniati Husniati; Baiq Niswatul Khair (Jurnal Pijar Mipa, 2021)
This research aims to produce quality domino card learning media products. This type of research is research and development with the ADDIE model. The ADDIE model consists of several stages, namely analysis, design, development, implementation, and evaluation. The test subjects in this study were six fourth-grade Elementary School students, SDN 08 Mataram Lombok Indonesia, with category two students with high ability, two people with medium ability, and two students with low ability. The research data were obtained using a media feasibility test, validation questionnaire for media experts, material experts, student response questionnaires, and teacher responses. Based on the trial results, it was obtained data on the results of student responses percentage of 94.3%, which were included in the "very good" criteria, and the results of teacher responses percentage of 100%, which were included in the "very good" category. The results of the expert validation obtained a percentage of 85%, which was included in the "very good" criteria, and the results of the material expert validation percentage of 100% were included in the "very good" criteria. The domino card learning media for the fourth-grade elementary school students can be said to be valid and suitable for use in learning.